Gestión integral de residuos sólidos : el análisis multicriterio como herramienta para la selección de alternativas en un contexto de transición tecnológica : el caso de Cañuelas - Rodriguez Alonso, Santiago Manuel (2018)
The municipal solid waste management of the Municipality of Cañuelas shows deficiencies, the collection does not cover all of its areas, there is an open-air dump for final disposal and the so-called "Ecopuntos" for separation and recycling have not been established. \nIn this work, it is proposed to study and select alternatives for the treatment and final disposal of solid urban waste for Cañuelas through a Analytic Hierarchy Process, taking into account social, political, economic and environmental criteria of the Municipality.\nBased on considering the currently existing treatment alternatives worldwide and analyzing them in the context of the Metropolitan Region of Buenos Aires with experts in the subject, the following alternatives to be evaluated were selected: Sanitary Landfill, Separation in Origin and Recycling, Biological Mechanical Treatment Plant and energy recovery of waste. \nOnce the alternatives were selected, between March 2014 and October 2016, 230 surveys were carried out involving the urban, rural and closed-neighborhood population and 12 interviews involving political and economic actors and technical experts. \nTaking into account the alternatives to be evaluated, the criteria considered and the results of the surveys and interviews, the rest of the multicriteria analysis steps were completed, that is, modeling, valorisation, prioritization and synthesis and sensitivity analysis. \nThe Analytic Hierarchy Process carried out showed that the best option is the Separation in Origin and Recycling, followed by the Traditional Sanitary Landfill, later by the Biological Mechanical Treatment Plant and finally, the Energy Valorization of the Waste. Separation in origin and recycling almost doubled the preference (0.422) with respect to the alternative obtained in second place, sanitary landfill (0.230). This result is explained given that the separation in origin and recycling weighs with greater value the environmental and social criteria that are the criteria that were the most important in the analysis. The model was very consistent so the result obtained is very far from being random and the dynamic sensitivity analyzes performed did not modify the result obtained. \nThe Analytic Hierarchy Process proved to be an extremely powerful tool for decision-making especially to evaluate various alternatives in relation to numerous criteria, with complex variables to compare as it occurs in the integral management of urban solid waste. According to its results, it is imperative to move from the open dump to the sanitary landfill at the same time that environmental awareness and education plans must be implemented for the separation at source and the adaptation of the necessary infrastructure for the separation plant/s "Ecopuntos". In the medium / long term, alternatives such as TMB should be considered. \nThe population is aware of the need for separation and recycling and is very predisposed to collaborate in its implementation. On the other hand, the allocation of economic resources of the current waste management should be reviewed given that it is feasible to improve it, specifically in the case of collection to achieve 100% coverage. All these changes must be strongly directed by the responsible political sector, taking it as a state policy that must transcend its own management.